Parents' knowledge, attitude, and practices toward methamphetamine abuse among youth and its risk factors in Saudi Arabia - Amaal A Ibrahiem; Munerah M Al Dawsari; Reem E Almeaqli; Ali A Keshk; Nasir A Ali; Hussain Habil (Wolters Kluwer Medknow Publications, 2024)
Objective: The present study aimed to conduct an assessment of parents' knowledge, attitudes, and practices toward methamphetamine "shabu" abuse among youth and its risk factors. Materials and Methods: The present cross-sectional descriptive study was conducted on a sample of 1179 parents. Parents were assured that questionnaire content would stay classified and was given anonymously. It had 20 demographic, drug use, and addiction treatment questions. Statistical Package for Social Sciences v. 24 and Chi-Square test were used to examine the data after evaluating and coding it. Results: Out of a total of 1179 participants, only 11% had not heard about shabu, about 38% did not know the main symptoms of crystal addiction, and 46% did not know the long side effects of crystal addiction. The majority of participants mentioned that shabu is available in powder format (57%) or liquid (13%), while 27% did not know its form. Most of the participants (97%) think that the drug of shabu or crystal or ice is dangerous; about 60% of participants mentioned that there is an addict in the family. Conclusion: Parents have good knowledge levels regarding different aspects of methamphetamine or shabu abuse, symptoms, and its risk factors. Further in-depth studies are needed at whole Saudi Arabia.